2005
DOI: 10.1002/prs.10072
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of temperature‐dependent lower flammability limit of pure organic compounds in air at atmospheric pressure

Abstract: An equation is proposed for the accurate and user‐friendly estimation of the lower flammability limit (LFL) of C/H, C/H/N, C/H/O, C/H/O/N, and monohalogenated organic pure compounds in air at atmospheric pressure in the 25–400° C temperature range. The equation derived in this study used 40 chemicals (LFLs) for the derivation and over 200 for the validation. Comparisons between experimental data and estimated data show that the average absolute deviation is <10%, and that deviations ≥20% are exceptions. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…When heated, some Mediterranean plants produce and emit VOC related to their secondary metabolism [37,38]. These compounds possess a low ignition temperature [39]. As the density of VOC is higher than the density of air when vegetation is heated by the sun or by an approaching fire, the emitted VOC would be released and could accumulate near the ground and below the vegetation layer or flow down slope to the bottom of a canyon.…”
Section: Gas Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…When heated, some Mediterranean plants produce and emit VOC related to their secondary metabolism [37,38]. These compounds possess a low ignition temperature [39]. As the density of VOC is higher than the density of air when vegetation is heated by the sun or by an approaching fire, the emitted VOC would be released and could accumulate near the ground and below the vegetation layer or flow down slope to the bottom of a canyon.…”
Section: Gas Accumulationmentioning
confidence: 99%
“…The emitted gases trapped into the enclosure were sampled thanks to adsorbent tubes and analysed by gas chromatography and gas spectrometry. Then, the lower flammability limit was estimated as a function of the temperature of the enclosure [39]. The study showed that generally the VOC concentrations were under the flammability limit, except for heat fluxes over 15 kW/m 2 and enclosure temperatures above 170°C.…”
Section: Gas Accumulationmentioning
confidence: 99%
“…These methods can be divided into four categories: empirical equations [19][20][21], critical flame temperature correlations [22,23], structural group contribution methods [24] and neural network methods [25]. As empirical equations are easy to use (i.e.…”
Section: Flammability Limits Of a Volatile Organic Compounds Mixturementioning
confidence: 99%
“…Due to their lower values of Lower Flammability Limits (LFLs) than the unburned products [6], it is more likely that the "gas or dust explosion" encountered in accelerating forest fires are initiated by the combustion of VOCs/CO/air mixture. Indeed, some Mediterranean vegetal species (e.g.…”
Section: Introductionmentioning
confidence: 99%